Penggunaan Indeks Harga dalam Menganalisis Pergerakan Harga Komoditas Pangan di Indonesia Periode 2017-2023 - Melindah, Devi; Wulan, Elis Ratna (Future Science, 2024)
This research aims to explore the effectiveness of using index prices in analyzing commodity price movements during a certain period. Through historical analysis and statistical methods, this research aims to deter-mine the extent to which index numbers can be used as an analytical tool in commodity markets. The methods used include the Laspeyres, Paasche and Ideal Fisher price index formulas. This research will also present case examples and discuss the results to provide deeper insight into the potential for using index numbers in analyzing commodity price movements with the hope of contributing to better understanding in commodity market analysis and decision making.